Comparative ploidy response to experimental hydrogen peroxide exposure in Atlantic salmon (Salmo salar). Issue 81 (October 2018) - Chalmers, Lynn; Vera, Luisa M.; Taylor, John F.; Adams, Alexandra; Migaud, Herve
Abstract: While research into the growth, survival, nutrition and, more recently, disease susceptibility of triploid Atlantic salmon has expanded, there remains an overall lack of studies assessing the response of triploids to chemical treatments. It is essential that the response of triploids to disease treatments be characterised to validate their suitability for commercial production. This study aimed to investigate and compare the stress and immune responses of triploid and diploid Atlantic salmon following an experimental treatment with hydrogen peroxide (H2 O2 ). A dose response test was first undertaken to determine a suitable test dose for both diploid and triploid Atlantic salmon. Following this, diploids and triploids were exposed to H2 O2 (1800 ppm) for 20 min, as per commercial practices, after which blood glucose and lactate, and plasma cortisol and lysozyme were measured, along with the expression of oxidative stress and immune-related genes. In the first 6 h post-exposure to H2 O2, comparable mortalities occurred in both diploid and triploid Atlantic salmon. Cortisol, glucose and lactate were not significantly influenced by ploidy suggesting that, physiologically, triploid Atlantic salmon are able to cope with the stress associated with H2 O2 exposure as well as their diploid counterparts. Exposure to H2 O2 significantly elevated the expression of cat and sod2 in diploid livers and gr, il1β and crp/sap1b in diploid gills, while it significantly decreased the expression of saa5 and crp/sap1a in diploid gills. In triploids, the expression levels of cat, hsp70, sod1, saa5, crp/sap1a and crp/sap1b in liver was significantly higher in fish exposed to H2 O2 compared to control fish. The expression of gr, sod1 and il1β in triploid gills was also elevated in response to H2 O2 exposure. This study represents the first experimental evidence of the effects of H2 O2 exposure on triploid Atlantic salmon and continues to support their application into commercial production. Highlights: This study represents the first testing of H2 O2 in triploid Atlantic salmon. Following H2 O2 exposure, triploid and diploid Atlantic salmon showed similar levels of cortisol, glucose and lactate. Ploidy differences in gene expression may be linked to extra genetic material in triploid cells, but requires further study.